Rising Self-Reliant: PT Pertamina EP Rantau Field’s Efforts to Realize Inclusive Empowerment through the Rumah Kreatif Tamiang Program - Putranto, Nurseno Dwi; Rahmadani, Rara Ayuni; Kusuma, Oscar Mudha (INFLUENCE: INTERNATIONAL JOURNAL OF SCIENCE REVIEW, 2023)
In the past decade, efforts to respect the rights of persons with disabilities have become a concern across all sectors, including the private sector. Persons with disabilities continue to face challenges related to their livelihood and well-being. This study aimed to describe the efforts of the private sector company PT Pertamina Rantau Field in realizing Inclusive Empowerment through the CSR program known as Rumah Kreatif Tamiang. The study employed a qualitative methodology, utilizing both primary and secondary data sources. Primary data was gathered through interviews with beneficiaries, while secondary data was sourced from the company’s internal records and relevant research journals. The findings of this study indicate the following: (1) The company plays a significant role in the development of vulnerable communities and is comprehensively responsive to these issues, as demonstrated by PT Pertamina EP Rantau Field. (2) Persons with disabilities are prepared to reintegrate into society by applying the skills acquired through the Rumah Kreatif Tamiang program, which includes workshop skills, handicrafts, and café management. (3) The Rumah Kreatif Tamiang Program contributes to poverty alleviation among persons with disabilities through their active involvement and support, facilitated through collaboration among various stakeholders, including the government, private sector, NGOs, and the community.